ASSESSMENT OF THE IMPACT OF FLY ASH ON THE TECHNOLOGICAL AGING OF BITUMEN IN THE ASPHALT BINDER SYSTEM - V.I. Kaskiv; O.V. Sokolov; V.V. Mozghovyi (World Science, 2024)
In Ukraine, about 30% of all electricity is generated from the combustion of solid fuels such as coal, oil shale, and peat. In our country, there are about 15 operating thermal power plants that generate about 5-6 million tons of ash and slag waste per year. Thus, the fuel and energy sector waste generated in the furnaces of thermal power plants is a huge accumulation of ash in the form of dusty residues and lumpy sludge, as well as various ash and slag mixtures. These products of high-temperature treatment (1200 °C - 1700 °C) of the mineral part of the fuel are widely used in many countries of the world, and given the global trend towards an increase in the share of the secondary market for waste, we should predict an increase in the rate of their processing in Ukraine. In Ukrainian practice, asphalt concrete is mainly used as a mineral powder obtained by grinding carbonate rocks in accordance with DSTU B V.2.7-119 and DSTU B V.2.7-121. At the same time, millions of tons of dusty waste - fly ash - are generated at Ukrainian power generating enterprises as a result of coal combustion. This material meets the requirements of DSTU B V.2.7-121 and can be used for the production of asphalt mixtures. However, it has not been sufficiently studied how fly ash affects the technological aging of bitumen. The aim of this study is to evaluate the effect of fly ash aggregates on the technological aging of bitumen in the asphalt binder system in comparison with traditional mineral powders of various origins. It was found that fly ash is close to the performance of limestone aggregate and can be used as an asphalt filler in asphalt concrete. As a result of the laboratory studies and analysis of the results of the impact of technological aging on the asphalt binder, we can state that the aging index of asphalt binder with fly ash is intermediate between limestone mineral powder and granite dust and is close to that of asphalt binder with limestone mineral powder. This may indicate that the use of fly ash as a mineral powder in asphalt mixtures will not negatively affect their technological aging. Other studies of the physical and mechanical properties of asphalt concrete with fly ash performed by the authors allow us to conclude that fly ash, as a material, is suitable for use as an aggregate for asphalt concrete mixtures.